Single‐Molecule Magnetic, Catalytic and Photoluminescence Properties of Heterometallic 3d–4f [Ln{PZn2W10O38(H2O)2}2]11− Tungstophosphate Nanoclusters. Issue 37 (17th September 2021) - Das, Vivek; Khan, Imran; Hussain, Firasat; Sadakane, Masahiro; Tsunoji, Nao; Ichihashi, Katsuya; Kato, Chisato; Inoue, Katsuya; Nishihara, Sadafumi
Abstract: A series of eleven lanthanide containing di‐Zinc (II) substituted heterometallic 3 d –4 f sandwich‐type tungstophosphate nanoclusters [Ln{PZn2 W10 O38 (H2 O)2 }2 ] 11− (Ln=Nd III, Sm III, Eu III, Gd III, Tb III, Dy III, Ho III, Er III, Tm III, Yb III, and Lu III ) have been synthesized by a single step reaction procedure. These clusters were characterized by various analytical techniques such as single crystal X‐ray diffraction (SC‐XRD), fourier transform infrared (FT‐IR) spectroscopy, high‐resolution electro‐spray ionization mass spectrometry (HR‐ESI‐MS), inductively coupled plasma atomic emission spectroscopy (ICP‐AES), solid UV/Vis, photoluminescence spectroscopy, powder X‐ray diffraction (P‐XRD) and thermogravimetric analysis (TGA). All the polyanions are isostructural and consists of a lanthanide ion sandwiched between two units of ( 1, 5 ) isomer of di‐Zn substituted α ‐Keggin type tungstophosphate. The complexes Sm‐2 a, Eu‐3 a, Tb‐5 a, and Dy‐6 a show good photoluminescence behavior. The catalytic properties were examined for the oxidation of thioethers. The catalyst is stable with a high turn over frequency (TOF) of 6250 h −1 and can be recovered even after 5 consecutive cycles. Furthermore, magnetic properties revealed that Gd‐4 a, Tb‐5 a, Dy‐6 a, Er‐8 a, and Yb‐10 a show single‐molecule magnetic properties. Abstract : A series of heterometallic 3 d –4 f tungstophosphate nanoclusters have been synthesized. Some of the complexes show excellent catalytic activity for thioether oxidation, single molecule magnets and photoluminescence properties.